Integrating Yoga Sessions and Its Perceived Impact on Students’ Behaviour: A Case of Teenage Students in Pakistan (KASBIT Business Journal, 2020)
This study aimed to experiment if the implementation of the yoga exercises within the school timings may assist the educators in overcoming the problematic behaviour of teenaged students. To experiment, private-run elite schools in Pakistan were approached to seek their consent to gather data from teachers and parents of teenaged students regarding their behaviour before and after their exposure to yoga sessions, lasted for three months. The behaviour of students was measured using an adapted questionnaire initially developed as “Students Behaviour Survey” by Lacharand Gruber (2018) and PT teachers in the selected schools were provided with a complete guideline how to conduct the yoga sessions before measuring the behaviour of students. The results found to reveal a statistically significant difference between the behaviour of teenaged students before and after the yoga sessions. The integration of yoga sessions in school timings is perceived to bring positive change in the behaviour of teenaged students. Individuals involved in the teaching-learning process at schools in Pakistan including teachers, parents, students and school management are recommended to emphasize the integration of yoga sessions in school timings.
Keywords: students’ behaviour; teenage students; yoga sessions; yoga therapy